Why should anyone be led by you? : what it takes to be an authentic leader - Goffee, Robert; Jones, Gareth, 1951 August 21- (Boston, Massachusetts : Harvard Business Review Press, 2015)
Are you an authentic leader? Too many companies are managed not by leaders but by mere role players and faceless bureaucrats. What would it take to replace these empty suits with real leaders--men and women who are confident in who they are and what they stand for and who truly inspire people to achieve extraordinary results? Rob Goffee and Gareth Jones argue that leaders don't become great by aspiring to a list of universal character traits. Rather, effective leaders are authentic: they deploy individual strengths to engage followers' hearts, minds, and souls. Authentic leaders are skillful at consistently being themselves, even as they alter their behavior to respond effectively to changing contexts. In short, the authors present a powerful case: that it takes "being yourself, in context, with skill" to be a successful, authentic leader--and they show you how to do exactly that. In this lively and practical book, Goffee and Jones draw from extensive research to reveal how to hone and deploy your unique leadership assets while managing the inherent tensions at the heart of successful leadership: when to show emotion and when to withhold it, how to get close to followers while maintaining an appropriate role distance, and maintaining your individuality while "conforming enough" to gain traction and lead change. Underscoring the inherently social nature of leadership, the book also explores how leaders can stay attuned to the needs and expectations of followers. Why Should Anyone Be Led by You? will forever change how we view, develop, and practice the art of leadership, wherever we live and work.
Introduction: Why should anyone be led by you? -- Be yourself-more-with skill -- Know and show yourself-enough -- Take personal risks -- Read-and rewrite-the context -- Remain authentic-but conform enough -- Manage social distance -- Communicate-with care -- Authentic followership -- The price and prize of leadership -- Appendix A: Evaluating your leadership potential -- Appendix B: Maximizing authenticity and skill.
"With a new preface by the authors."
Previous edition: 2006.
Includes bibliographical references (pages [227]-235) and index.
Print version record.
Added to collection customer.56279.3
Keywords: Leadership; Leadership; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books